Positive and negative impacts of a meat tax on society : The case of Sweden - Berger, Valerie Friederike (2020)
Meat consumption and its societal effects have been of high interest to researchers, policy makers and the public in recent years. Meat provides both utility to the individual, as well as imposes externality cost on society. This thesis aims to investigate both sides, compare them and discuss which outweighs which. For this, Sweden as a case study was investigated, due to the amount of research existing and the country’s own interest in the topic. The paper bases its conclusions on extensive literature review, a research questionnaire and quantitative models. The results showed that both significant externality cost and utility exist. The research further proved, that a tax on meat could reduce the amount consumed but would also decrease the consumer’s welfare. However, the cost of meat may outweigh the utility lost. The conclusion can be drawn that incentivising a reduction in meat consumption may be justified, but due to the complexity of the topic, further research would be required.